Mechanical characterization of basalt woven fabric composites: numerical and experimental investigation (Fracture and Structural Integrity, 2014)
Basalt fabric composite, with different twill wave reinforcements, i.e. twill 2/2 and twill 1/3, have been studied in this work by means of experimental tests and numerical finite element (FE) simulations. As fabric reinforcements show repeating undulations of warp and fill yarn, simple mixtures law cannot be applied.As a consequence, the mesoscopic scale, lying between the microscopic and the macroscopic one, has to betaken into account to mechanically characterize a fabric reinforced composite. The aim of this work is toevaluate the stiffness of a fabric reinforced composite in warp and fill direction. In particular a numerical FEmodel, assuming elliptical sections and sinusoidal shape of the yarns, has been implemented and experimentaltests have been carried out in order to validate the proposed model. Finally, the strength and the failure modesof the composite material, for each analysed structure and textile orientation, have been experimentallyinvestigated.
Keywords: Fabric reinforcement